2011
DOI: 10.1080/10286020.2011.605062
|View full text |Cite
|
Sign up to set email alerts
|

Gambogenic acid inhibits proliferation of A549 cells through apoptosis inducing through up-regulation of the p38 MAPK cascade

Abstract: Gamboge is a dry resin secreted from Garcinia hanburryi, and gambogenic acid (GNA) is one of the main active compounds of gamboge. We have previously demonstrated the anticancer activity of GNA in A549 cells and pointed out its potential effects in anticancer therapies. Previous studies reported that GNA induced apoptosis in many cancer cell lines and inhibited A549 tumor growth in xenograft of nude mice in vivo. However, the anticancer mechanism of GNA has still not been well studied. In this paper, we have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…glioblastoma cells, 49 breast cancer, 50 lung cancer 51 Gambogenic acid is associated with inhibition of proliferation of A549 cells by apoptosis induction and cell-cycle arrest, 48,52,53 and Medulloblastoma, 60 lung cancer cells, 61 blood cancer cells, colon cancer cells, breast cancer cells, brain cancer cells, ovary cancer cells, kidney cancer cells, prostate cancer cells 62,63 Triptolide can inhibit cell proliferation and arrest the cell cycle, 64 increase LC3α expression levels, 65 and inhibit the PI3K-Akt-mTOR pathway. while eRK1/2 is activated, autophagy of cell death is induced.…”
Section: U251mentioning
confidence: 99%
“…glioblastoma cells, 49 breast cancer, 50 lung cancer 51 Gambogenic acid is associated with inhibition of proliferation of A549 cells by apoptosis induction and cell-cycle arrest, 48,52,53 and Medulloblastoma, 60 lung cancer cells, 61 blood cancer cells, colon cancer cells, breast cancer cells, brain cancer cells, ovary cancer cells, kidney cancer cells, prostate cancer cells 62,63 Triptolide can inhibit cell proliferation and arrest the cell cycle, 64 increase LC3α expression levels, 65 and inhibit the PI3K-Akt-mTOR pathway. while eRK1/2 is activated, autophagy of cell death is induced.…”
Section: U251mentioning
confidence: 99%
“…Afterward, apoptotic cell was identified by double supravital staining with recombinant fluorescein isothiocyanate (FITC)-conjugated Annexin-V and PI, using the Annexin V-FITC apoptosis detection kit (Becton Dickinson, Canaan, CT, USA) according to manufacturer's instructions (Cheng et al, 2011). In short, SMMC-7721 cells were harvested by gently adding trypsin and rinsed twice with cold PBS.…”
Section: Assessment Of Apoptosis On Smmc-7721 Cells By Annexin-v/pi Dmentioning
confidence: 99%
“…Gambogenic acid (GEA) is another active component of gamboge which exhibits cytotoxicity and anti-inflammatory activity (19,20). The molecular mechanisms that underlie the effects of GEA include induction of cell cycle arrest (21,22), apoptosis (21,(23)(24)(25)(26)(27), autophagy (22,28), necroptosis (29) and chemosensitivity (29,30). Herein, we demonstrated that GEA induced rapid proteasome-mediated degradation of CIP2A.…”
Section: Introductionmentioning
confidence: 99%